2005
DOI: 10.1161/01.hyp.0000165672.69176.ed
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Office, Home, and Ambulatory Blood Pressure to Blood Glucose and Lipid Variables in the PAMELA Population

Abstract: Abstract-Alterations in blood glucose and cholesterol are more frequently detectable in hypertensive than in normotensive conditions. However, no information exists as to whether this phenomenon involves only office or also home and 24-hour ambulatory blood pressure (ie, when values are representative of daily life). In 2045 subjects enrolled in the Pressioni Arteriose Monitorate E Loro Associazioni (PAMELA) study, we measured home, 24-hour, and office blood pressure. Measurements also included fasting blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 34 publications
9
44
0
13
Order By: Relevance
“…26 Recently, Julius et al reported that in a randomized prospective study including 809 participants in the highnormal BP category, the absolute reduction in the incidence of new-onset hypertension at 2 years with candesartan was 26.8%, as compared with 8% with lifestyle intervention. 27 That result implies the need for additional studies to evaluate the clinical outcome of more active treatment in the high-normal BP group.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, Julius et al reported that in a randomized prospective study including 809 participants in the highnormal BP category, the absolute reduction in the incidence of new-onset hypertension at 2 years with candesartan was 26.8%, as compared with 8% with lifestyle intervention. 27 That result implies the need for additional studies to evaluate the clinical outcome of more active treatment in the high-normal BP group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that there is a close relationship between BP values and metabolic alterations: in the PAMELA population [30] Mancia et al observed a positive correlation between serum total cholesterol and all BP values. However, the prevalence and clinical implications of the WCE in the Lipid Clinic setting was never investigated.…”
Section: Discussionmentioning
confidence: 98%
“…This issue is relevant to understanding whether elevated SUA levels may impair the efficacy of blood-pressure lowering therapy, and/or urate lowering therapy should be associated with antihypertensive drugs. The analysis of data from the PAMELA study showed that several metabolic factors, such as blood glucose and total cholesterol, might interact with blood-pressure control, suggesting that additional metabolic factors should be evaluated 15 . The possible role of SUA was studied in a cohort of 2191 subjects enrolled in a survey (Brisighella Heart Study), among whom 146 new cases of arterial hypertension and 394 treated but uncontrolled hypertensive patients with different levels of SUA were identified 16 .…”
Section: Impact Of Serum Uric Acid On Blood-pressure Lowering Therapymentioning
confidence: 99%